The Role of Customer Satisfaction as a Mediator of Service Quality and Purchase Intentions in E-Commerce in Indonesia - Sudarto, sudarto (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose –The purpose of this research is to see how the quality of an online store's website affects consumer satisfaction, repurchase intention, and consumer satisfaction as a mediating of consumer repurchase interest. Methodology/approach –This study was done in June 2021 in Tarakan, with a sample of 110 participants who had made transactions utilizing an online store application. An online survey on a Likert scale of 1 to 5 was used to collect data. In this work, path analysis was used as an analytical technique (path analysis). Findings –Service quality has a substantial positive effect on customer satisfaction, service quality has a significant positive effect on repurchase interest, and customer satisfaction has a significant positive effect on repurchase interest, according to the findings of the study. Novelty/value –Service quality plays a very significant role in e-commerce.